Feasibility Studies on Utilization of Low-Pressure in Hydro-pneumatic Driveline - F., Wasbari; R. A., Bakar; Gan, Leong Ming; M. A., Salim (Penerbit UTEM, 2016)
The aim of this paper is to present a feasibility study on the use of low pressure in vehicle’s small applications. Hydro-pneumatic driveline is one of the hybrid sub-systems for hydraulic hybrid vehicle. Usually, the energy supplied by hydro-pneumatic accumulator/storage operates through maximum energy level to a minimum. This often reaches to the point where the limit of minimal operations is higher than the pre-charge limit. The remaining power is claimed as not effective to move a vehicle, but the pressure still contains energy. Therefore, it is a waste of energy. The pressure energy can be used to power vehicle’s small applications such as fan, starting motor, compressor, hybrid electric battery charger, and others. Hence, a laboratory-scale experiment was extended away to see the hydro-pneumatic drive system behavior to operate at low-pressure level. Through the experiment, it was found that the system can work at low-pressure level. However, the power generated was 740 watt, 16.2 Nm theoretical torque and operated at 52 % efficiency at a pressure of 50 bar. This value is too small if compared to the force needed to move the vehicle. Still, it was dependable enough to power the small application in the vehicle sub-system. Through this research, it is hoped that the ineffective pressure of the hydraulic hybrid vehicle can be utilized so it can contribute to the increase of efficiency.